The Effectiveness of Realistic Job Previews for UK Graduate Schemes - Carver, F. L. (2018)
This research examines the effectiveness of Realistic Job Previews (RJPs) for UK graduate schemes. This research was undertaken because low graduate retention is an issue commonly faced by organisations, therefore by establishing the extent to which RJPs can be viewed as effective within this context, this issue could be reduced. Semi-structured telephone interviews were carried out with a sample of eight participants who are all currently enrolled onto a UK graduate scheme and received RJPs within the recruitment process for the scheme. Participants were asked to discuss their experiences within the recruitment process, the RJP they received, and how this compares to the reality of their graduate scheme. The effectiveness of RJPs was measured in four themes, with the emergence of subsequent sub-themes. The four themes were as follows: reducing ambiguity; delivery of the RJP; affecting the decision to stay within the recruitment process; and affecting the decision to stay within the organisation. The results showed that RJPs could be viewed as effective in the sense that they could reduce ambiguity amongst job applicants, if delivered by a fellow graduate currently on the graduate scheme and played an important role in affecting decisions to stay within or leave the organisation on completion of the graduate scheme. However, the results showed that RJPs could not be deemed as effective with regards to affecting a job applicant’s decision to stay within or leave the recruitment process. As a result, organisations should consider the reasoning behind the use of an RJP within the recruitment process, when delivering this to job applicants.